Energization: A decentralized energy development option - Oliveros, Alfredo (1994)
Traditionally, and particularly at election time, the governments in power (and candidates) offer to "electrify" by extending electrical networks or installing stationary groups to solve energy problems in many towns in the interior of the country, without analyzing that there are better options. This predisposition is then expressed in practices that have not left a satisfactory experience in our countries (Park, 1988; Oliveros, 1991; Clave, 1988; ITDG, 1988).